Annual review of comparative and international education 2019 - Wiseman, Alexander W. (International perspectives on education and society ;, 2020)
Since 2013, the Annual Review of Comparative and International Education has covered the significant developments in the field of comparative and international education. The Annual Review of Comparative and International Education 2019 begins with a collection of reflection essays about comparative education trends and directions written by both professional and scholarly leaders in the field. Topics covered in the 2019 volume include major theoretical and methodological developments, reports on research-to-practice, area studies and regional developments, and the diversification of comparative and international education. A special introductory chapter builds on the assumption that scholarship and professional practice in comparative and international education often supports and encourages inclusiveness, interdisciplinarity, and contextualization in research and in the field. However, the introductory chapter interrogates the assumption that comparative and international education scholars and professionals promote these same concepts of gender equality, empowerment, and inclusiveness in the field itself.